DARYIA YAROSLAVSKA`S NOVEL "A GIRL IN NEW YORK": SEARCHING NATIONAL IDENTITY - Kasiyan, Z. L. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
The article first attempts to analyze the artistic peculiarities of “A Girl in New York” novel by Ukrainian diaspora writer Daria Yaroslavska, the specifics of the solution to the problem of "I" – "Other" as the search for the main heroine of her own identity in the coordinates of the New World. The problem of assimilation of personality under the influence of "Other", preservation of "His", transformation into "another-but-your" is considered. Particular attention is paid to the dynamics of the development of the image of the Ukrainian emigrant.